Loss of SETD2 aggravates colorectal cancer progression caused by SMAD4 deletion through the RAS/ERK signalling pathway - Ma, Chunxiao; Liu, Min; Feng, Wenxin; Rao, Hanyu; Zhang, Wei; Liu, Changwei; Xu, Yue; Wang, Ziyi; Teng, Yan; Yang, Xiao; Ni, Li; Xu, Jin; et al. (Clinical and translational medicine, 2023)
Backgound Colorectal cancer (CRC) is a complex, multistep disease that arises from the interplay genetic mutations and epigenetic alterations. The histone H3K36 trimethyltransferase SET domain‐containing 2 (SETD2), as an epigenetic signalling molecule, has a 5% mutation rate in CRC. SETD2 expression is decreased in the development of human CRC and mice treated with Azoxymethane /Dextran sodium sulfate (AOM/DSS). Loss of SETD2 promoted CRC development. SMAD Family member 4 (SMAD4) has a 14% mutation rate in CRC, and SMAD4 ablation leads to CRC. The co‐mutation of SETD2 and SMAD4 predicted advanced CRC. However, little is known on the potential synergistic effect of SETD2 and SMAD4. Methods CRC tissues from mice and SW620 cells were used as research subjects. Clinical databases of CRC patients were analyzed to investigate the association between SETD2 and SMAD4. SETD2 and SMAD4 double‐knockout mice were established to further investigate the role of SETD2 in SMAD4‐deficient CRC. The intestinal epithelial cells (IECs) were isolated for RNA sequencing and chromatin immunoprecipitation sequencing (ChIP‐seq) to explore the mechanism and the key molecules resulting in CRC. Molecular and cellular experiments were conducted to analyze the role of SETD2 in SMAD4‐deficient CRC. Finally, rescue experiments were performed to confirm the molecular mechanism of SETD2 in the development of SMAD4‐dificient CRC. Results The deletion of SETD2 promotes the malignant progression of SMAD4‐deficient CRC. Smad4Vil‐KO; Setd2Vil‐KO mice developed a more severe CRC phenotype after AOM/DSS induction, with a larger tumour size and a more vigorous epithelial proliferation rate. Further mechanistic findings revealed that the loss of SETD2 resulted in the down‐regulation of DUSP7, which is involved in the inhibition of the RAS/ERK signalling pathway. Finally, the ERK1/2 inhibitor SCH772984 significantly attenuated the progression of CRC in Smad4Vil‐KO;Setd2Vil‐KO mice, and overexpression of DUSP7 significantly inhibited the proliferation rates of SETD2KO; SMAD4KO SW620 cells. Conclusions Our results demonstrated that SETD2 inhibits the RAS/ERK signaling pathway by facilitating the transcription of DUSP7 in SMAD4‐deficient CRC, which could provide a potential therapeutic target for the treatment of advanced CRC. SETD2 deficiency promotes the progression of SMAD4‐deficient CRC. SETD2 deletion exacerbates SMAD4‐deficient CRC via RAS/ERK signalling pathway. SETD2 inhibits the RAS/ERK signalling pathway by promoting DUSP7 transcription.